Klasyfikacja krajów świata pod względem poziomu PKB i zrównoważenia środowiskowego z wykorzystaniem statystyk pozycyjnych - Markowska, Małgorzata (Classification of World Countries Regarding GDP and Environmental Sustainability Level Using Positional Statistics, 2006)
The article presents an attempt of applying positional statistics for the classification of 146 world countries including the level of development measured by means of GDP per capita and Environmental Sustainability Index components, i.e.: environmental systems, environmental stress reduction, reduction of people susceptibility to environmental stress, social and institutional capabilities of reacting to environmental challenges as well as global management.The level of each ESI component correlation with GDP level per capita was also assessed.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonometria (17); 2006; nr 1123, s. 156-170